Post–Liver Transplant Lymphoproliferative Disorder Presenting as Biliary Stricture. Issue 7 (20th July 2021) - Karb, Daniel; Satyavada, Sagarika; Shah, Raj; Ismail, Mayada; Alencherry, Erin; Beck, Rose; Cohen, Stanley Martin
ABSTRACT: A 63-year-old man with nonalcoholic steatohepatitis cirrhosis who underwent orthotopic liver transplant presented 1 year later with obstructive jaundice because of a biliary stricture. This anastomotic stricture was initially believed to be ischemic, but further investigation revealed malignant biliary obstruction because of encasement of the bile duct by a mass arising from liver segment VII, later determined to be post-transplant lymphoproliferative disorder with widespread metastasis. After reduction of immunosuppression and systemic chemotherapy, he experienced complete remission. This case illustrates the need to consider post-transplantation lymphoproliferative disorder–related biliary stricture in any postorthotopic liver transplantation transplant patient presenting with obstructive jaundice.